Current situation and factors influencing elderly care in community day care centers: a cross-sectional study - Chen, Junyu; Zhu, Yuan; Song, Yulei; Liang, Yongqi; Wang, Lulu; Li, Weitong; Wang, Huimei; Xu, Guihua (Frontiers in Medicine, 2024)
Background: The latest census data show that people over 60 years of age account for about 18.7% of the total population in China and the aging of the population has become an irreversible trend in the 21st century. This study aimed to investigate the current status and factors influencing care of the elderly in community day-care centres to lay a foundation for development of better services in community day care centers.Methods: This study was a cross-sectional survey using convenience sampling in Nanjing, China. The survey instrument was the day-care Elderly care Demand Questionnaire, including the Ability of Daily Living Assessment (ADL), Shuiyuan Social Support Rating Scale (SSRS), day-care elderly care service demand List, and general information survey.Results: A total of 450 elderly people in day-care centres were surveyed. The elderly had different degrees of demand for day-care services, especially daily care. Correlation analyses indicated that age(r=0.619), education level (r=0.616), source of income (r=0.582), caregiver (r=0.557), satisfaction with care service (r=0.603), and degree of ADL (r=0.629) were correlated with the need for day-care services of the elderly (all P<0.05). The factors influencing the need for day-care services included age, education level, source of living, caregiver, satisfaction with service, and ADL (all P<0.05).Conclusions: Elderly care services in community day-care centres are mainly based on daily and spiritual comfort and the needs of the elderly are influenced by many factors. Timely nursing care policy and measures targeted on those factors are needed to improve the elderly care.